Hubungan Pola Asuh Demokratis dengan Kecerdasan Sosial pada Remaja Pengguna Smartphone di SMA 4 Bojonegoro: The Relationship between Democratic Parenting Patterns and Social Intelligence in Smartphone Using Adolescents at SMA 4 Bojonegoro - MOCH NUR HUDA; Zaki Nur Fahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid expansion of smartphone use among students has become a significant concern in educational and developmental psychology due to its association with social behavior and interpersonal competence. Specific Background: Excessive gadget engagement during school age may be related to students’ social intelligence, which includes the ability to interact, empathize, and adapt within peer environments. Knowledge Gap: Although numerous studies discuss smartphone addiction and learning motivation, limited empirical evidence specifically examines its statistical relationship with students’ social intelligence in formal school settings. Aims: This study aims to analyze the correlation between smartphone use and students’ social intelligence. Results: The findings indicate a statistically significant relationship between the intensity of smartphone use and the level of social intelligence, as demonstrated by correlation analysis. Novelty: The study provides empirical data focusing specifically on social intelligence as a developmental construct within the context of contemporary digital behavior. Implications: These findings underline the importance of parental supervision, balanced digital habits, and educational guidance to support students’ interpersonal development in the digital era. Keywords: Smartphone Use, Social Intelligence, Students, Digital Behavior, Quantitative Correlation Key Findings Highlights: Statistical analysis reveals a significant association between device engagement and interpersonal competence. Higher intensity of mobile technology exposure corresponds with variations in peer interaction ability. Empirical evidence supports the relevance of digital behavior in developmental psychology research.